Pembelajaran Al-Qur’an dengan Metode An-Nahdliyah pada Era Pandemi Covid-19 (Studi Kasus di TPQ Al-Mubarok Dusun Sri Lestari Kampung Sriwijaya Mataram) - Rohman, Syaifur (Sekolah Tinggi Agam Islam Sumatera Medan, 2021)
The method is an important part of the learning component, including learning the Qur'an. Uniquely, in the Bandar Mataram District area, they began to apply a